Hepatoprotective effect of aqueous extract of Melothria perpusilla against carbon tetrachloride induced liver injury in albino rats - Yengkhom, Nokul S.; Gunindro, Ngangom; Kholi, Sania M.; Moirangthem, Rakesh S.; Rajkumari, Bharati D. (International Journal of Research in Medical Sciences, 2017)
Background: In absence of reliable hepatoprotective drug in modern medicine, the traditional herbal medicines have been emphasized. Present study was designed to assess hepatoprotective effect of aqueous extract of Melothria perpusilla (AEMP) against carbon tetrachloride (CCl4) induced liver injury. Methods: Five groups of animals with 6 rats in each were treated for 7 days. Group I received 1% gum acacia in distilled water (1 ml/200 g p.o.) daily. Group II, III, IV and V received CCl4 in liquid paraffin (1 ml/kg s.c.) on day 2, 4 and 6. Group III, IV and V were treated respectively with silymarin (100 mg/kg p.o.), AEMP- 200 and 400 mg/kg p.o. daily. On day 8, liver injury was assessed by measuring serum ALT, AST, ALP and bilirubin. Results: ALT, AST, ALP and bilirubin were significantly reduced in groups receiving both CCl4 and AEMP when compared with CCl4 treated group. Conclusions: AEMP produced hepatoprotective effect against CCl4 induced liver injury.